The role of order and disorder in thermal and material sciences part 1: Heat and society - Šesták J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The notion of heat is thoroughly analyzed and its historical links are searched particularly with relation to both the Greek philosophy (Milesians, Pythagoreans, atomists, etc.) and in the present day thermal physics. Fluctuation, spontaneity and chaos are discussed. Thermodynamics is reviewed in the relation to both the traditional development and the modern description of disequilibria (open systems). Effect of dissipation is shown often to provide new, self-organized structures. Exploitation of fire and its conscious use as a manufacturing power are analyzed in terms of generalized engines to act in the sense of the information transducers.